Planning Occupational Safety and Health Management System (OSHMS) Based on The Covid-19 Pandemic Guidance at So Good Food Dairy Company - Ali Al Farisi; Mirwan Ushada; Moh. Wahyudin (Agroindustrial Journal, 2022)
Companies need an Occupational Safety and Health (OSH) culture based on a new life guidance during the Covid-19 pandemic. The application of OSH at So Good Food Dairy Company is moderate, though there are no control measures to minimize this risk. This study further aimed to analyze the application of OSH in the workplace and determine the implementation of the OSH Management System (OSHMS). Furthermore, it focused on identifying the probability of accidents at each workstation and proposed risk mitigation plans and anticipatory steps. Questionnaires were then administered to collect primary data from 62 respondents at the So Good Food Dairy Company’s processing, filling, packing, and storage workstations. Similarly, secondary data were obtained from documented information about the company’s OSH. All the respondents provided valid answers with a Cronbach alpha value of 0.9671, considered very reliable. Moreover, the questionnaire responses showed that So Good Food Dairy Company was rated highly by workers. Failure Mode and Effects Analysis (FMEA) was used to identify the factors causing work accidents and Risk Priority Number (RPN), while recommendations for improvement were made based on the Hazard Identification Risk Assessment & Risk Control (HIRARC) principles. A total of 12 probability accidents were observed in processing, four in filling and packing, and six in storage. Therefore, this study proposes an OSH design that includes an OSHMS planning based on clauses ISO 45001:2018 and ISO/PAS 45005:2020. Additionally, seven OSH programs and a risk mitigation road map using the Pareto Chart principle to set priorities were recommended.